Pragmatic Discourse of Givenness and Adverbial Clauses: Applied Linguistics Research Articles and Thai Undergraduate Students’ Writing - Wongkittiporn, Abhinan (JET (Journal of English Teaching), 2024)
This study examines the correlation between the theory of pragmatic discourse of givenness and CP adverbial clauses from the two datasets: Q1 SCOPUS applied linguistics research articles and Thai undergraduate students’ writing. The first set was 24 applied linguistics research articles from journals of English for Specific Purposes and English for Academic Purposes. There were 45 tokens of adverbial clauses. Another set of data collection was 35 participants, majoring in English, whose English proficiency was A2 or elementary based on their Oxford Placement Test. The second dataset contained 31 tokens of CP adverbial clauses in descriptive and narrative writing. Data was analyzed using Pearson Correlation in SPSS29. The first section showed there was a statistically significant relationship between the theory of pragmatic discourse of givenness and CP adverbial clauses in applied linguistics research articles where the p-value was reported at 0.011. The reasons why CP adverbial clauses are used are due to giving the arguments from previous studies. This implied that the SCOPUS writers knew well how to use CP adverbial clauses regarding form, functions and genre. In contrast, the results in the second dataset showed there was a statistically significant relationship between the CP adverbial clauses and non-givenness produced by Thai undergraduate students where the p-value was reported at 0.001. Accordingly, Thai private university students whose English proficiency was elementary used CP adverbial clauses arbitrarily; non-reasonable. This implies that they knew form, but they did not know what are the function CP adverbial clauses which were applied in different genres. It is expected that the results in this study will help Thai undergraduate students improve their usage of CP adverbial clauses accurately and appropriately.